Penerapan Konsep Non-Deterministic Finite Automata (NFA) pada Aplikasi Simulasi Mesin Kopi Vending - Richardson, Benny; Hendy, Kevin; Andiyani, Ventryshia; Philips, Wilson (Teknik Informatika Universitas Pamulang, 2019)
In this research, an application for the simulation of vending coffee machines will be discussed using the concept of Non-Deterministic Finite Automata (NFA). With the projected growth in coffee consumption in Indonesia, which increases every year, vending machines can be one of the innovations that can be applied to coffee machines. This coffee vending machine can make 6 coffee variants, with its temperature and desired glass size. There is also a system of cash payments that are applied to this vending coffee machine, where the change will be issued according to the excess balance that is available. The method used is the formal method, to link the design of formal specifications with the application flowchart. Based on the test results obtained, the concept of Non-Deterministic Finite Automata (NFA) can be used as an alternative in the design of vending coffee machines.